KAJIAN PENURUNAN MUTU DAN UMUR SIMPAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) SEGAR DALAM KEMASAN PLASTIK POLYPROPYLENE PADA SUHU RUANG DAN SUHU RENDAH - Mutiara Cahya; Rofandi Hartanto; Dwi Dian Novita (The University of Lampung, 2014)
Oyster mushroom is one of commodites that has prospect to be developed in Indonesia. In case of fresh oyster mushrooms usually have a short shelf life due to high moisture content and are still experiencing respiratory process, so as to speed up the process of deterioration. Packaging with polypropylene plastic packaging is one method of storage to maintain freshness and shelf life of oyster mushroom. The purpose of this study is to examine and determine the rate of decline in the quality and shelf life of fresh white oyster mushrooms in plastic packaging polypropylene at room temperature and low temperature during storage.This research was conducted in two phases, namely the measurement of respiration rate experiments and storage of fresh oyster mushrooms in plastic containers in different volumes at room temperature and low temperature. Parameters observation in this study that changes in weight, projected area is reduced crown circumference, discoloration, water content, respiration rate and shelf life.The results showed that the oyster mushroom storage in polypropylene plastic packaging can maintain the rate of decline in the quality and shelf life of fresh white oyster mushrooms either at room temperature or low temperature. Water content and the highest weight changes during storage in plastic containers at room temperature are both on day 3 and 7 at low temperature that is equal to 92.81%, 150.52 g, 91.76%, and 130.79 g . Control oyster mushrooms at room temperature and low temperature had the highest respiration rates at the 24th and 48th in the amount of 230.48 and 239.53 mg. CO2/kg.hour. Oyster mushrooms in packaging stored at room temperature (31˚C) can last up to 5 days and 14 days at low temperature (9˚C). Keywords: Oyster Mushrooms, polypropylene plastic, storage temperature, packaging, respiration rate